Speculation on an early Pleistocene origin of the Parker dunes of southwest Arizona, USA - Seong, Yeong Bae; Shandonay, Kenzie L.; Dorn, Ronald I.; Gootee, Brian F.; Yu, Byong Yong (Elsevier, 2024)
The Parker Dunes in western Arizona, USA represent the largest dune system in the Sonoran Desert. This study presents a simple 10Be-26Al cosmogenic burial age of 1.90 +/- 0.20 Ma, obtained from well cuttings 240-270 m deep in Butler Valley, just east of the dune field. Given the large errors associated with burial dating, we can only speculate that this oldest known aeolian sediment within the Parker Dunes is roughly concurrent with the Bat Cave flood event ca. 2.1 Ma of the nearby Colorado River, as well as regional climatic aridity during the early Pleistocene. Since older dune deposits may be present at other locations in the Parker Dunes, its origin dates back to at least the early Pleistocene. The more important, broader implication rests in highlighting the underutilized potential of well cuttings as a sediment source for cosmogenic burial dating in aeolian research.